NEEDS ANALYSIS OF LEARNING ENGLISH: WHAT ARE ISLAMIC BOARDING SCHOOL STUDENTS’ VOICES? - Suryani, Irma; Dalimunte, Ahmad Amin (Premise: Journal of English Education and Applied Linguistics, 2023)
This study attempts to determine and analyze the need for ESP learning materials among boarding school students. A needs analysis must be conducted to determine these needs so that students receive the essential materials to support their present learning process or future jobs. The study employed a qualitative approach and a descriptive methodology. An Islamic boarding school's second-grade students comprise the research sample. The instruments of data collection research were questionnaires and interviews. The data are in the form of qualitative techniques taken from the questionnaires, interviews, and observation. Using descriptive methods, the researchers examined the data using percentages. The study's findings indicate that the demands of students living in dorms for ESP English lessons are pretty diversified. Thus, they require English not only for their immediate needs but also for their future careers as international speakers and interpreters. Since the needs of ESP learners are constantly evolving, it is advised that ESP English teachers and other interested parties be able to meet the needs of their students and conduct a needs analysis regularly.